Adenosquamous Carcinoma of Skene’s Gland: A Case Report and Literature Review - Gao, Qian; Liu, Xiaoyun; Ye, Lin; Lv, Tingting; Teng, Yanyi; Lan, Jian; Li, Tingchao; Tian, Min; Chen, Juqi; He, Shanshan; Xie, Shengyan; Zou, Yan (Frontiers in Oncology, 2022)
Skene's gland is homologous to the male prostate and can secrete prostate fluid. However, Skene's gland carcinoma is extremely rare, with only 20 cases reported in the literature thus far. We report the first case of adenosquamous carcinoma of Skene's gland. The patient was a 54-year-old woman who was admitted to our hospital due to vaginal bleeding and a vaginal mass, accompanied by multiple lymph nodes and vulvar metastases. She had a history of dysuria and episodic hematuria for 2 years. Contrast-enhanced pelvic MRI showed a mass in the right labia majora and swelling of the right inguinal lymph nodes. In addition, a mass in the anterior vaginal wall surrounded the urethra and grew in a semi-encircled manner. After receiving neoadjuvant chemotherapy, MRI revealed that the mass surrounding the urethra had shrunk, and the nodular shadow of the right labia majora was larger than before. The patient underwent elective surgery. Surgical pathology showed adenosquamous carcinoma, and immunohistochemistry suggested intestinal differentiation. Forty-six days after surgery, the patient subsequently died of tumor consumption and organ insufficiency due to cerebral infarction, recurrence, and multiple metastases. This paper describes the clinical, radiological, and histopathologic features as well as the prognosis of the rare disease adenosquamous carcinoma of Skene's gland. In addition, we briefly review the published literature.